Importance Of Packaging Design Elements In Choosing Local Brands By Foreigners In Malaysia - Sharififar, Foroozan (2011)
The study aims to understand the importance of packaging design elements on choosing local brand by foreigners. The main purpose of this study is to investigate the relationship between packaging design elements (Graphic and color, Size, and Shape, Product Information, and Technology) and consumer purchase decision. It is proposed that the four Packaging design elements, would impact on the foreigner purchase Decision in Malaysian market. The significant predators by four formulated hypotheses.